An easy death - Harris, Charlaine (Harris, Charlaine. Gunnie Rose., 2018)
"Set in a fractured United States, in the southwestern country now known as Texoma. A world where magic is acknowledged but mistrusted, especially by a young gunslinger named Lizbeth Rose. Battered by a run across the border to Mexico Lizbeth Rose takes a job offer from a pair of Russian wizards to be their local guide and gunnie. For the wizards, Gunnie Rose has already acquired a fearsome reputation and they're at a desperate crossroad, even if they won't admit it. They're searching through the small border towns near Mexico, trying to locate a low-level magic practitioner, Oleg Karkarov. The wizards believe Oleg is a direct descendant of Grigori Rasputin, and that Oleg's blood can save the young tsar's life..."--